Peer effects of enterprise green financing behavior: Evidence from China - Yang, Songling; Zhang, Huining; Zhang, Qiuyue; Liu, Tingli (Frontiers in Environmental Science, 2022)
Green finance is critical for adjusting the industrial structure and promoting sustainable economic development; therefore, it is important to understand enterprise green investment and financing behavior. This study aims to investigate the peer effects of enterprise green financing behavior. Based on theoretical analysis, this study selected data from Chinese A-share listed companies from 2011 to 2020 as the research sample. In this study, the fixed effects model was used to examine the peer effects of enterprise green financing. Meanwhile, a moderating effect model was employed to explore the function of the economic policy uncertainty and corporate social responsibility commitment on peer effects of enterprise green financing. The results show that the enterprise’s green financing behavior increases significantly with its peer companies’ (i.e., other companies in the same industry or the same region) green financing behavior, and responds to peer companies’ characteristics in the same industry, indicating peer effects on green financing behavior. The peer effects of enterprise green financing are stronger when the economic policy uncertainty is higher, suggesting that the green financing behavior of peer companies reduces external uncertainty by providing comprehensive and useful information, thus enhancing the enterprise’s information environment and enabling it to make better green financing decisions. Moreover, peer effects are more pronounced when corporate social responsibility commitment is higher, indicating that peer companies’ higher performance in social responsibility can improve their information transparency and build good reputation, increasing the enterprise’s disclosure and reputation costs in the capital market. Therefore, our findings highlight the importance of peer effects in enterprise green financing behavior. To enhance the enterprises’ green financing behavior and promote green finance development, the government should focus on the industrial and regional situation to conduct green finance and promote the overall green financing behavior of enterprises by establishing typical enterprises or pilot cities.